If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(6x + 10y) + 8 = 0 (6x * 2 + 10y * 2) + 8 = 0 (12x + 20y) + 8 = 0 Reorder the terms: 8 + 12x + 20y = 0 Solving 8 + 12x + 20y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + 12x + -8 + 20y = 0 + -8 Reorder the terms: 8 + -8 + 12x + 20y = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 12x + 20y = 0 + -8 12x + 20y = 0 + -8 Combine like terms: 0 + -8 = -8 12x + 20y = -8 Add '-20y' to each side of the equation. 12x + 20y + -20y = -8 + -20y Combine like terms: 20y + -20y = 0 12x + 0 = -8 + -20y 12x = -8 + -20y Divide each side by '12'. x = -0.6666666667 + -1.666666667y Simplifying x = -0.6666666667 + -1.666666667y
| 4(x-6)-10=2x | | b=11-a | | 2(x-4)-6=-6(-2x+4)-6x | | 6r+5=55 | | k+3=6+k | | 30+(.0825*30)+(15%*30)= | | 6(y+2)=-2(8y-7)+6y | | -26+26=-15p-10p | | 11x-4=5x+9 | | x*12=-2 | | X+3(4)=48 | | 3x+10=3x+4+1 | | 2(x-1)-3x=8 | | 8-2x=2x-5x | | 1x+3(4)=48 | | 9(-10)+160= | | -6h+2=-46 | | x+7=-3+3x | | .60x+.30(90)=.50(x+90) | | 6=18b | | 3x+15=12b-3b | | x*-5=10 | | 16t^2-128+400=0 | | 2a+24-3a=5a | | 8p-4=7p-2 | | n^2-34n-251=0 | | t^2-8+25=0 | | 1-m=1-m | | 16.28+8=100 | | -4n+2=-13-7n | | x^7-5x+6=0 | | 13x+23y=-5 |